Expression of Aspergillus niger CAZymes is determined by compositional changes in wheat straw generated by hydrothermal or ionic liquid pretreatments - Daly, Paul; van Munster, Jolanda M.; Blythe, Martin J.; Ibbett, Roger; Kokolski, Matthew; Gaddipati, Sanyasi; Lindquist, Erika; Singan, Vasanth R.; Barry, Kerrie W.; Lipzen, Anna; Ngan, Chew Yee; Petzold, Christopher J.; et al. (Springer, 2017)
Background